Kepemimpinan dan Organisasi dalam Optimalisasi Sumber Daya Manusia di SD Negeri 2 Muntang, Kemangkon, Purbalingga - Tri Antini; M. A. Hermawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the role of leadership and organizational culture in optimizing human resources (HR) at SD Negeri 2 Muntang, Kemangkon, Purbalingga. Using a qualitative approach through library research, the study explores various literature related to leadership, organizational culture, and human resource management in educational institutions. The findings indicate that leadership plays a crucial role in shaping a positive and supportive organizational culture. Different leadership styles—democratic, delegative, laissez-faire, and authoritarian—have varying impacts on teacher motivation and performance. The study further emphasizes that a strong and conducive organizational culture significantly enhances teacher performance and fosters an effective learning environment. At SD Negeri 2 Muntang, the combination of appropriate leadership styles and a positive organizational culture has successfully optimized teacher performance, enabling the school to achieve its educational goals more effectively. Thus, the synergy between leadership, organizational culture, and human resource management is a key factor in the overall success of educational institutions.